A four-microRNA panel in serum may serve as potential biomarker for renal cell carcinoma diagnosis - Li, Rongkang; Chen, Wenkang; Lu, Chong; Li, Xinji; Chen, Xuan; Huang, Guocheng; Wen, Zhenyu; Li, Hang; Tao, Lingzhi; Hu, Yimin; Zhao, Zhengping; Chen, Zebo; et al. (Frontiers in Oncology, 2023)
Background Renal cell carcinoma (RCC) is one out of the most universal malignant tumors globally, and its incidence is increasing annually. MicroRNA (miRNA) in serum could be considered as a non-invasive detecting biomarker for RCC diagnosis. Method A total of 224 participants (112 RCC patients (RCCs) and 112 normal controls (NCs)) were enrolled in the three-phrase study. Reverse transcription quantitative PCR (RT-qPCR) was applied to reveal the miRNA expression levels in RCCs and NCs. Receiver operating characteristic (ROC) curves and the area under the ROC curve (AUC) were utilized to predict the diagnostic ability of serum miRNAs for RCC. Bioinformatic analysis and survival analysis were also included in our study. Results Compared to NCs, the expression degree of miR-155-5p, miR-224-5p in serum was significantly upregulated in RCC patients, and miR-1-3p, miR-124-3p, miR-129-5p, and miR-200b-3p were downregulated. A four-miRNA panel was construed, and the AUC of the panel was 0.903 (95% CI: 0.847–0.944; p < 0.001; sensitivity = 75.61%, specificity = 93.67%). Results from GEPIA database indicated that CHL1, MPP5, and SORT1 could be seen as promising target genes of the four-miRNA panel. Survival analysis of candidate miRNAs manifested that miR-155-5p was associated with the survival rate of RCC significantly. Conclusions The four-miRNA panel in serum has a great potential to be non-invasive biomarkers for RCC sift to check.